The Effect of seasonal variations, covariations with minerals and forage value on Itchgrass’ foliar silicification from Sudanian Benin - KINDOMIHOU, M. VALENTIN; SINSIN, Brice; HOLOU, R.A.Y.; AMBOUTA, KARIMOU JEAN-MARIE; ADJOLOHOUN, SÉBASTIEN; HOUINATO, MARCEL ROMUALD BENJAMIN; GRUBER, W.; HERBAUTS, J.; LEJOLY, Jean; MEERTS, P. (My University, 2016)
Silica (SiO2) in forage grasses has been found in reducing cell-wall digestibility. This study investigates whether: (i) the seasonal variability affects the silica and minerals accumulation and forage values of leaves of R. cochinchinensis and (ii) silica concentration is correlated with minerals and fodder value. In an Itchgrass population selected in the W Biosphere Reserve, leaves were collected on 90 marked plants from May to October 2003 and 2004, at 15 days intervals except May, June and October. Some 300 g of fresh blades from the 3rd most recently expanded leaves were oven dried and analyzed for dry mass, SiO2, ash, N, Na, Ca, P, K, Mg. Digestible Nitrogen Matter (DNM) and Fodder Energetic Value (FEV) were calculated using Demarquilly formula. Apart from SiO2, Ash and forage value, data were log-transformed to restore homoscedasticity before Statistical analyses. SiO2 ranges from 5.69 % to 9.95 %, i.e. varying 1.4 fold between May and October, reaching 1.75 fold at mid-September. SiO2 positively related to Ca but negatively to K, P, N, DNM and FEV. The negative correlations suggest that SiO2 concentration in R. cochinchinensis could be reduced with a significant increase in energy and accumulation of important nutrients such as N, P and K. Therefore, leaf silicification and nutritive value relationship should be conclusive in the case of Itchgrass.
Keywords: Rottboellia cochinchinensis; Silicification; Minerals; Seasonal variations; Forage value; Covariations; Sudanian Benin